Characterisation of corrosion-induced crack in concrete using ultrasonic diffuse coda wave - Cheng, Weixia (2023)
Corrosion damage in reinforcing steel bars has been a major cause of cracking and spalling of reinforced concrete. To extend the service life of concrete structures, non-destructive testing methods are necessary to assess the corrosion status in order to conduct a timely repair. At the early stage of corrosion, rust grows from the reinforcing bar, subsequently generates cracks towards the surface of the concrete. Ultrasonic methods have been widely used to detect cracks in concrete. However, it is challenging to characterise them due to the heterogeneous material properties of the concrete. In this paper, ultrasonic imaging technique based on diffuse coda wave has been explored to inspect and characterise corrosion-induced cracks. In this method, scattering cross-section of the crack is reconstructed with the Locadiff imaging technique. Based on the assumption that both crack tips have the same scattering cross-section, the size of the crack can be estimated when the location of the reinforcing bar is known. Numerical simulations were carried out to image straight and curved cracks, showing excellent accuracy. Experiments were designed subsequently on concrete samples with accelerated corrosion. The induced cracks were characterised by the proposed ultrasonic method, and compared with X-ray CT results, showing very good agreement.